Apiary: An OS for the Modern FPGA - Lim, Katie; Giordano, Matthew; Zhang, Irene; Kasikci, Baris; Anderson, Thomas (2025 Workshop on Hot Topics in Operating Systems, 2025)
Many datacenter operators have deployed FPGAs as hardware accelerators because their reconfigurability allows them to be repurposed as the application mix changes. Directly attaching the FPGA to the network further reduces latency, improves cost-performance, and reduces energy use relative to mediating network communications with CPUs. However, building accelerated applications or services for direct-attached FPGAs is challenging, especially with the complex I/O and multi-accelerator capacity of modern FPGAs. To address this, we propose Apiary, a microkernel operating system for direct-attached FPGA accelerators. The key idea in Apiary is to raise the level of abstraction for accelerated application code, with security, virtualization, threaded execution, and interprocess communication provided by the hardware OS layer.